Rewilding education? Exploring an imagined and experienced outdoor learning space. Issue 3 (3rd May 2020) - Bates, Charlotte
ABSTRACT: This paper follows the progress of a small rural primary school in the UK as it goes about cultivating a new vision of the future by transforming its outdoor spaces. Exploring the significance of these outdoor spaces as they are imagined, made and experienced, from the first design stages to the first days of use, the paper considers how feelings about children's access to and engagement with nature are entangled with cultures of protection and surveillance. Using observations from a multimodal ethnography, including video tours and photography workshops alongside observant participation and interviews, the paper illustrates how, in practical terms, changing an educational landscape can also shift a school culture, giving children greater freedom outdoors to live, learn and grow together.